Corrosion inhibition potential of new oxo-pyrimidine derivative on mild steel in acidic solution: Experimental and theoretical approaches - AlFalah, Mothana Ghazi Kadhim; Yilmazer, Mehmet Izzettin; Freigita, Khalid Saad Milad; Saracoglu, Murat; Kokbudak, Zulbiye; Kandemirli, Fatma (Elsevier BV, 2024)
Through electrochemical impedancetesting and potentiodynamic polarisation, it was investigated how a material atambient temperature might prevent corrosion.1-(5-(4-Methoxybenzoyl)-4-(4-methoxyphenyl)-2-oxopyrimidin-1(2H)-yl)-3-(4-chlorophenyl)urea (MMOP) was used as a corrosion inhibitor on mild steel samples in 1 M HCl.With a maximum inhibition efficacy of 97.6% (at immersion period of 72 h andconcentration of 5×10-4 M), the inhibitor used was shown to be anexceptional corrosion inhibitor. Based on the findings of potentiometricpolarization, this substance falls within the category of mixed inhibitorssince corrosion inhibition was accomplished by the inhibitor adhering to themetal. Adsorption of investigated MMOP completely followed Langmuir adsorptionisotherm and adsorption can be categorized as physisorption–chemisorption, witha value of ΔGads of -35.6 kJ.mol-1. In order to confirmthe effectiveness of the protective coating applied to the mild steel surface,we analysed the protective layer through the utilization of Atomic ForceMicroscopy (AFM) and Scanning Electron Microscope (SEM) / Energy DispersiveX-ray spectrometry (EDX). The density functional theory (DFT) and Monte Carlosimulation (MCS) approaches were used to investigate the relationship betweenmolecular structure and inhibitory efficacy. The results suggest that theinhibitor in issue could be a new approach to reducing mild steel corrosionunder harsh circumstances and long immersion times.